Perceived Performance on Tutors During Process of Certification in Four Teacher Training Institutions in Durango - Sánchez, Diana María Espinosa; López, Miguel Ángel Muñoz; Luna, Edgar Jarib Castro (European Journal of Multidisciplinary Studies, 2018)
Higher Education Institutions (HEI) currently face a major issue: low levels of certification and thus the terminal efficiency. The present research emerged on the need to know what the perceived performance of tutors on postgraduate levels during the certification process in four teacher training institutions in the State of Durango. The research has a quantitative approach. This work is presented both as descriptive and explanatory. The methodology used is survey, which was used as a technique and an instrument. Variables were considered to building up 177 items, with an Alpha Cronbach reliability = .93. A total of 85 students were surveyed, who are the total of students on process to obtain the MA degree on Education in the four institutions where the research was conducted. These institutions also hold the Institutional Tutoring Program (ITP). Some common traits on tutors were found, which may strengthen or weaken the process of certification; also, some factors that make certification difficult.